Using System Dynamics to Study the Effect of Change Orders on Labor Productivity - Gharib, Shrouk (AUC Knowledge Fountain, 2021)
Change orders in construction projects lead to numerous negative impacts, including loss of labor productivity, delays, and cost overruns. Owners and contractors are usually in disagreement when it comes to allocating the extent of responsibilities with respect to the resulting overruns. Each party tries to hold the other party fully responsible for such overruns through a series of claims and disputes. Several delay analysis techniques have been developed to aid in settling such disputes, however, they do not fully grasp the rippled impacts of change orders and do not assist parties in reaching consensus when it comes to finding the isolated rippled impacts of each change order. This research aims to develop a framework that supports delay analysis based on dynamic modeling with a focus on the impacts of change orders. System dynamics is utilized as the base modeling methodology due to its capability of capturing rippled impacts and complex interrelations. A novel calibration methodology is also developed to enable using this framework in any construction project. After development and verification, the framework was tested on a sample construction project that faced delays due to change orders. The developed model was able to quantitatively link the productivity losses and delays to each change order, which helped in clearly allocating the responsible parties for the delays. In addition, several what-if-scenarios were conducted to enhance the understanding of how such impacts could have been avoided. This research is envisaged to support owners and contractors in quickly reaching consensus regarding the impacts of change orders; thus, minimizing the corresponding disputes and fostering a healthier contracting environment.